An Analysis of Islamic Law Regarding Default Judgments in Divorce Action Cases: Case Study of Judgment No. 13/Pdt.G/2022/PA.Smg - Ramadhan Novrizky; Danny Prasetyo; Muhammad Auliya Rahman; Rafli Rafli (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the structural intersection of statutory civil procedures and classical Islamic jurisprudence through a rigorous doctrinal analysis of Semarang Religious Court Decision Number 13/Pdt.G/2022/PA.Smg. Adopting a non empirical qualitative approach, the investigation isolates the operationalization of a default judgment within a brief marriage characterized by immediate spousal abandonment and the complete non appearance of the defendant. The findings reveal that the judiciary successfully balanced rigid civil procedural requirements with material Sharia doctrines, specifically employing the classical legal maxim of harm prevention to justify immediate dissolution. Furthermore, the imposition of a Talak Satu Ba’in Sughra decree establishes crucial gender equity by stripping the absent husband of unilateral reconciliation rights and restoring the individual autonomy of the plaintiff. This adjudication demonstrates a progressive jurisprudential evolution within Indonesian religious courts, where formal mechanics are harmonized with substantive justice frameworks to prevent structural domestic oppression. Ultimately, the study underscores the necessity of proactive judicial intervention to protect vulnerable spouses from legal limbo, ensuring that statutory family law actively reinforces constitutional protections and contemporary human rights standards.